Istri yang Bekerja dalam Perspektif Al-Quran Studi Penafsiran M. Quraish Shihab terhadap Kata Qawwam dalam QS. An-Nisa/4:34 dan Penafsiran QS. Al-Ahzab/33:33 - Rahma, Nur Fadhillah (ANWARUL, 2024)
Nowadays, in households, very large and urgent economic needs often become a problem in the household, making the wife play a role in meeting daily needs. Moreover, nowadays, where the price of goods and the cost of living are getting higher and higher, making the wife have no other choice but to look for work outside the home, even though her "heart" doesn't want to work. Based on this, this research aims to find out how Al- Koran regarding this matter by looking at the views of M. Quraish Shihab in QS. An-Nisa / 4:34 and the interpretation of QS Al-Ahzab / 33:33. This research is included in library research (Library Research), namely research carried out using literature (library) in the form of the book Al-Misbah, as well as books, theses or journals that study related to working wives which are descriptive analysis, namely analyzing the interpretation of Al-Misbah. Misbah. The approach used in this research is the Maudhu'i interpretation method (thematic) approach, namely looking at themes related to the meaning of the word qawwam in the Koran. The method used is content analysis, namely analyzing the interpretation of mufassir figures regarding the meaning of the word qawwam in the Koran. Based on the results of research that the author has conducted, the author found that M. Quraish Shihab allows his wife to work, sometimes even working is obligatory if the job requires it and he also needs the job, with the condition; with the husband's permission, the work is carried out in a respectful and polite atmosphere. So that they maintain their religion, and can also avoid the negative impacts of this work on themselves and their environment.